Danon disease in women: a modern view of the problem: a case series - R. P. Myasnikov; D. A. Nefedova; N. N. Kuzina; O. V. Kulikova; E. V. Gagarina; E. A. Mershina; O. M. Drapkina (Российский кардиологический журнал, 2024)
Introduction. Danon disease is a rare cardiomyopathy (CMP) with multisystem involvement, which is associated with lysosome-associated membrane protein 2 (LAMP2) gene polymorphisms. This protein is the most important regulator of autophagy and is produced mainly in the myocardium, skeletal muscles and brain. This is reflected in the classic disease triad: hypertrophic CMP, skeletal myopathy and cognitive impairment. Danon disease is characterized by maximum penetrance regardless of sex. Expressivity is much less predictable in women, given the X-linked dominant inheritance and mosaicism of cellular production of the LAMP2 protein as a result of random inactivation of one of the X chromosomes.Brief description. The article presents two clinical cases demonstrating different disease courses in women with Danon disease. The analysis of case records, clinical performance, paraclinical data were carried out.Discussion. In recent years, the widespread development of molecular genetic diagnostics and imaging methods has led to the accumulation of data on natural course and prognosis of Danon disease. It became clear that in female patients with Danon disease, previously considered mainly as mutation carriers, clinical manifestations can vary from low-symptom phenotypes with isolated CMP to severe multisystemic involvement and early onset. Raising awareness among practitioners about the Danon disease specifics in women, multidisciplinary examination, and genetic testing are the basis for timely diagnosis, risk stratification, and treatment initiation.